QR codes in use : the experience at the UPV Library - Pons Chaigneau, David Marcelo; Vallés Navarro, Raquel; Abarca Villoldo, Marta; Rubio Montero, Francisco José (Serials: The Journal for the Serials Community, 2011)
QR codes are beginning to be introduced in our libraries and are an easy way to give additional information to mobile web users in a given time and place. In this paper, we share the experience and give some examples of the introduction and use of QR codes at the Universitat Politècnica de València (UPV) Libraries in Spain.We describe how we use QR codes to give access to our mobile website, to download documents and to promote our literature blog.We also describe how we promote our QR codes to both users and librarians, including some best practices. Finally,we discuss our future projects, such as the use of QR codes for information literacy. Pons Chaigneau, DM.; Vallés Navarro, R.; Abarca Villoldo, M.; Rubio Montero, FJ. (2011). QR codes in use : the experience at the UPV Library. Serials. 24(3 - Suplement). doi:10.1629/24S47 24 3 - Suplement Taiga Forum Steering Committee, Taiga Forum Provocative Statements, 2006: a href="http://www.taiga-forum.org/Provocative Statements_2006.pdf" target="_blank" >http://www.taiga-forum.org/Provocative Statements_2006.pdf /a> (accessed 15 August 2011). Ashford R, QR codes and academic libraries: Reaching mobile users, C&RL News, 2010, 71 (10), 526–530: a href="http://crln.acrl.org/content/71/10/526.full" target="_blank" >http://crln.acrl.org/content/71/10/526.full /a> (accessed 15 August 2011). Hoy M, An introduction to QR codes: linking libraries and mobile patrons, Medical Reference Services Quarterly, 2011, 30 (3), 295–300. Hampton D, Reaching mobile users with QR codes, Kentucky libraries, 2011, 75 (2), 6–10. Burns E, Remaking the library information hunt using QR codes, Pennsylvania Library Association Bulletin, 2011, 66 (1), 11–13. Arroyo-Vázquez N, Web móvil y bibliotecas, El Profesional de la Información, 2009, 18 (2) 129–136: a href="http://hdl.handle.net/10760/13057" target="_blank" >http://hdl.handle.net/10760/13057 /a> (accessed 15 August 2011). Arroyo-Vázquez N, Informe APEI sobre movilidad, APEI, 2011: a ...